The Devil at the Edge of this Book: Intertextual Ecologies of Early Modern Crime Narratives - George, Emily (Early Theatre)

(untitled) (McMaster University Library Press / Becker Associates, 2023)
This essay uses The Wonderfull Discouerie of Elizabeth Sawyer and The Witch of Edmonton to examine how the multiple, conflicting agendas and intertextual relationships of crime narratives in popular print and professional drama manifest on both the space of the page and of the stage. Considering paratexts as part of the intertextual ecology of early modern crime narratives as they move between print and stage reveals materialized ambivalence about the relationships among the narratives themselves; the audiences consuming, circulating, and reproducing those narratives; and the criminals whose voices are both marginalized and authoritative in the story.